2012
DOI: 10.4330/wjc.v4.i12.312
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial and progenitor cells: Evidence from acute and long-term exercise effects

Abstract: Circulating bone-marrow-derived cells, named endothelial progenitor cells (EPCs), are capable of maintaining, generating, and replacing terminally differentiated cells within their own specific tissue as a consequence of physiological cell turnover or tissue damage due to injury. Endothelium maintenance and restoration of normal endothelial cell function is guaranteed by a complex physiological procedure in which EPCs play a significant role. Decreased number of peripheral blood EPCs has been associated with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 125 publications
(196 reference statements)
1
54
1
1
Order By: Relevance
“…Fourth, we cannot definitively exclude that a reduced EPC number is unique to HFpEF rather than related to its comorbidities. Finally, we did not test whether exercise, which could result in increased circulating EPC levels in healthy persons, influenced the EPC number in HFpEF patients [40]. Although a previous study showed endothelial dysfunction may not be related to reduced exercise capacity in HFpEF [23], further studies focusing on exercise characteristics should be designed to elucidate the exercise effects on EPCs in HFpEF.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Fourth, we cannot definitively exclude that a reduced EPC number is unique to HFpEF rather than related to its comorbidities. Finally, we did not test whether exercise, which could result in increased circulating EPC levels in healthy persons, influenced the EPC number in HFpEF patients [40]. Although a previous study showed endothelial dysfunction may not be related to reduced exercise capacity in HFpEF [23], further studies focusing on exercise characteristics should be designed to elucidate the exercise effects on EPCs in HFpEF.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Circulating endothelial cells (CECs) and endothelial progenitor cells (EPCs) have been proposed as non-invasive surrogate biomarkers of angiogenesis in cancer and other diseases (1)(2)(3)(4)(5). Their baseline number and kinetics in cancer patients has been widely investigated and several previous studies have demonstrated that they can be altered by disease status and treatments, including biological anti-angiogenic drugs and chemotherapy (CT) (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing number of EPCs has been established as an independent prognostic risk factor associated with endothelial dysfunction and high cardiovascular risk 11,12 . Patients with cardiovascular risk factors have shown a reduced number of circulating progenitors and an impaired Competing interests: none declared.…”
Section: Epcs and Copdmentioning
confidence: 99%